Economic profiles of Caribbean countries (UN ECLAC Port of SpainTT, 1999)
Provides economic profiles for 26 independent and non-independent countries of the Caribbean subregion. Seeks to present a succint snapshot of the economy of the respecive island under consideration, while also providing a time series of selected economic variables.
Keywords: ECONOMIC CONDITIONS